The Leverage Effect of Bank Disclosures - König, Philipp J.; Laux, Christian; Pothier, David (The Accounting Review, 2026)
ABSTRACT We study how disclosures affect banks’ leverage and risk. Banks screen borrowers and originate loans, partially financed using insured deposits. The possibility to sell loans before they mature incentivizes banks to lever up using uninsured short-term debt to dilute insured deposits. If markets are opaque, good loans trade at a discount, which limits banks’ use of short-term debt. If markets are transparent, prices compound information contained in disclosures, which leads banks to issue more short-term debt to further dilute insured deposits. We identify conditions under which the increase in leverage caused by disclosures reduces banks’ screening incentives. Our analysis has important implications for prudential regulation, including minimum regulatory capital requirements and leverage-based deposit insurance premiums. JEL Classifications: D80; G21; G14.